2020
DOI: 10.1002/gcc.22847
|View full text |Cite
|
Sign up to set email alerts
|

Novel renal medullary carcinoma cell lines, UOK353 and UOK360, provide preclinical tools to identify new therapeutic treatments

Abstract: Renal medullary carcinoma (RMC) is a rare, aggressive disease that predominantly afflicts individuals of African or Mediterranean descent with sickle cell trait. RMC comprises 1% of all renal cell carcinoma diagnoses with a median overall survival of 13 months. Patients are typically young (median age-22) and male (male:female ratio of 2:1) and tumors are characterized by complete loss of expression of the SMARCB1 tumor suppressor protein. Due to the low incidence of RMC and the disease's aggressiveness, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Initial analysis of these models confirmed the potential for combination therapy of bortezomib and cisplatin in RMC and highlighted other potential therapeutic options for patients with advanced RMC [73]. This study also identified a response in these cell line models to panobinostat, an HDAC inhibitor, that could affect the gene expression dysregulation as a result of loss of SMARCB1 [73]. In 2021, Alex et al developed the first metastatic pleural effusion (PE)-derived RMC PDX model [74].…”
Section: Limited Mouse Models For Rmcmentioning
confidence: 77%
See 1 more Smart Citation
“…Initial analysis of these models confirmed the potential for combination therapy of bortezomib and cisplatin in RMC and highlighted other potential therapeutic options for patients with advanced RMC [73]. This study also identified a response in these cell line models to panobinostat, an HDAC inhibitor, that could affect the gene expression dysregulation as a result of loss of SMARCB1 [73]. In 2021, Alex et al developed the first metastatic pleural effusion (PE)-derived RMC PDX model [74].…”
Section: Limited Mouse Models For Rmcmentioning
confidence: 77%
“…In 2019, Carugo et al developed a PDX from a patient with recurrent RMC [50]. In 2020, Wei et al developed two novel human cell line models, UOK353 and UOK360, which were derived from primary RMCs, and these had the ability to form tumors in mice [73]. These models provided a valuable tool for research and preclinical drug testing.…”
Section: Limited Mouse Models For Rmcmentioning
confidence: 99%
“…To more precisely compare the drug target expression of these tumors, further comparative studies are needed that may also involve other data dimensions such as the proteome. Moreover, cell line models that faithfully recapitulate the biology of RMCs are needed and have recently been established [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of these tumors, our study was clearly limited by the small number of samples included. A further, thorough characterization of these tumors is thus needed that also includes the comparability of the published cell line models [ 34 ] with their respective primary counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Assays were performed in triplicate and experiments were repeated three times in all five cell lines. Spheroids were successfully developed in three of the cell lines, UOK109, UOK120, and UOK124, using a previously described methodology [ 24 ] to evaluate 3D cell viability. Spheroids were incubated with drug for five days, before assessing viability by CellTiter-Glo 3D Cell Viability Assay (Promega).…”
Section: Methodsmentioning
confidence: 99%